Transmission dynamics of COVID-19 in Italy, Germany and Turkey considering social distancing, testing and quarantine - Serdar Gul; Kagan Tuncay; Baris Binici; Beyazit Bestami Aydin (Journal of Infection in Developing Countries)
Introduction: There are significant differences in the active cases and fatality rates of Covid-19 for different European countries.